2011
DOI: 10.1152/japplphysiol.01437.2010
|View full text |Cite
|
Sign up to set email alerts
|

Surface contamination artificially elevates initial sweat mineral concentrations

Abstract: Several sweat mineral element concentrations decline with serial sampling. Possible causes include reduced dermal mineral concentrations or flushing of surface contamination. The purpose of this study was to simultaneously sample mineral concentrations in transdermal fluid (TDF), sweat, and serum during extended exercise-heat stress to determine if these compartments show the same serial changes during repeat sampling. Sixteen heat-acclimated individuals walked on a treadmill (1.56 m/s, 3.0% grade) in a 35°C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 34 publications
9
49
0
1
Order By: Relevance
“…Several studies have shown that when serial samples are collected during exercise, initial sweat often has higher mineral concentrations than subsequent samples [99, 108111]. This is likely because initial sweat mixes with minerals trapped in the sweat pore or residing in the epidermis [112–115].…”
Section: Methodological Sources Of Variability In Sweating Rate and Smentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that when serial samples are collected during exercise, initial sweat often has higher mineral concentrations than subsequent samples [99, 108111]. This is likely because initial sweat mixes with minerals trapped in the sweat pore or residing in the epidermis [112–115].…”
Section: Methodological Sources Of Variability In Sweating Rate and Smentioning
confidence: 99%
“…The decrease in mineral concentrations observed throughout exercise is likely due to flushing of surface contamination. As Ely et al [99] have shown, meticulously cleaning the skin (with distilled water, soap, and a surgical scrub brush) prior to collection results in stable sweat mineral concentrations during 3 h of exercise (using the Parafilm-M ® pouch technique on the back).…”
Section: Methodological Sources Of Variability In Sweating Rate and Smentioning
confidence: 99%
See 3 more Smart Citations